Student-resourced service delivery of occupational therapy rehabilitation groups: patient, clinician and student perspectives about the ingredients for success. Issue 18 (28th August 2022) - Patterson, Freyr; Doig, Emmah; Fleming, Jenny; Strong, Jenny; Birch, Stephen; Whitehead, Mary; Laracy, Sue; Fitzgerald, Cate; Tornatore, Giovanna; McKenzie, Amy; Searles, Jacqueline; Pigott, Amanda
Abstract: Background: A number of innovative models of student practice placements are emerging due to pressures on universities to provide quality practice placements and on health services to deliver rehabilitation efficiently, safely and cost-effectively. The student-resourced service delivery (SRSD) group program is one such model in occupational therapy. There is a paucity of research evidence to guide services in planning, implementing and evaluating the SRSD model. Objective: The study aimed to explore and identify the factors that key stakeholders perceived as contributing to the successful development and implementation of the occupational therapy student-resourced service delivery group programs. Methods: Participants in this multi-site study were rehabilitation inpatients, clinicians, Clinical Education Liaison Managers and students completing practice placement in the student-resourced service delivery group program. Data were collected using face-to-face semi-structured interviews and focus groups. Results: A total of 83 participants consented to the study. Four themes emerged from the data. Planning needs to be an iterative process that commences before and continues during the program. Support processes need to be established for students and clinicians during and across placements. The creation of an engaging, client-relevant and graded group dynamic is critical for success. Establishing a culture whereby groups are valued by the clients, therapy and multidisciplinary teams is important. Conclusions: The above-mentioned factors were perceived as contributing to successful operationalisation of a student-resourced service delivery group program, and may be helpful when developing student-resourced service delivery professional practice placements in other settings. IMPLICATIONS FOR REHABILITATION: Student-resourced service delivery of groups are one way to achieve additional professional practice placements for students and delivery of therapy services for patients. Ongoing investment for planning and preparation, provision of continual support for students, a culture of valuing groups and students, and creating a group dynamic that engages group participants were perceived by stakeholders as key ingredients for successful implementation of the student-resourced service delivery group model. Clinicians and educators are encouraged to use the perceived success factors identified in this study as a resource for future student-resourced service delivery program development.